Social effects of the vote of the majority: A field-experiment on the Brexit-vote - Fernanda L. Lopez de Leon; Markus Bindemann (University of Kent, School of Economics, 2019)
The 2016 EU referendum result -the so-called Brexit vote- was widely perceived as a statement against immigration. We conducted a field-experiment to test whether the Brexit vote triggered anti-social attitudes. In a computerized quiz, our (non-deceptive) intervention randomized the information of whether the local majority voted to Leave or to Remain in the EU. We find that such information in support of Brexit increased negative attitudes towards immigrants. Moreover, the impactful treatments inhibited (rather than reinforced) individuals' pre-existing views to conform to the vote of the majority. Our findings provide insight into the effects of referenda results in changing individuals' attitudes.
Keywords: 330